THE PARTY IN RESIDENCE REGISTRATION PROCEEDINGS – DISCREPANCIES IN JURISDICTION OF ADMINISTRATIVE COURTS - Magdalena DREWNIANY (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2014)
In accordance with article 42 of the Code of Administrative Proceedings, the Party is a person whose legal interest or an obligation is connected to proceedings, or who demands some legal actions to be undertaken with regard to his or her legal interest or an obligation. The fundamental right of the Party is the right to participate in administrative proceedings underway. However, very often it is rather difficult to define the scope of entities whom the status of the Party can be granted. The aim of this paper is to present discrepancies at jurisdiction of administrative courts related to the meaning of the notion of the Party in case of residence registration proceedings. For many years the attribute of the Party was granted not only to the person who wished to de-register, but also to the owner of the premises or to any other entity who held a legal title of the premises. However, according to the line of jurisdiction with respect to residence registration which started to be formed after 2008, the above mentioned entities stopped to be considered as Parties. It was pointed out that the new jurisdiction was more sensible because of the formal nature of registration of population and the ex officio obligation to undertake proceedings to update the general register in such a way that it would reflect the actual residence of a given person under a given address. Considering the discrepancies at jurisdiction of administrative courts, the Ombudsman addressed the Supreme Administrative Court for clarification of the matter. According to the thesis of resolution taken by seven judges of Supreme Administrative Court on 5 December 2011, the person who holds a legal title to premises is granted the attribute of the Party within the meaning of article 28 of the Code of Administrative Proceedings, in administrative proceedings with respect to residence registration or de-registration of other people in the premises belonging to the Party.